Effectiveness of Animation Media Education on The Importance of The First 1000 Days of Life on Pregnant Women’s Knowledge - Putri Nelly Syofiah; Afrizal; Eka Putri Primasari; Putri Hadisti Khairani (International Health Sciences Journal, 2025)
Stunting is condition fail growing in children under 5 years old (toddlers) due to lack nutrition chronic marked​ with Length or tall his body be under​ standard . Data on stunting incidents shows that 21.6% of Indonesian children experience stunting in Indonesia. One of the method prevention Stunt is with increase knowledge Mother about attitudes and behavior Mother pregnant in prevent stunting incidents can done with giving animated video education. Purpose study This is know influence animated video education to knowledge Mother pregnant about prevention stunting.Design Pre- experimental research use one- group design pretest posttest Study​ This using purposive sampling technique. Population as many as 72 people and samples totaling 30 respondents. Research This has been implemented at the Ophir Health Center in the month of February until August 2024. Data collection was carried out on June 5 and 7, 2024. Data processing was carried out with the normality test , the data obtained is not normal, then Wilcoxon test was performed to obtain results Asymp.Sig = 0.000. Result study obtained on average before intervention 71.17 and average after intervention 88.17 with p value = 0.000 meaning <0.05 then influence effective video education to knowledge Mother pregnant at Ophir Health Center , West Pasaman . Conclusion of the study This is influence animated video education effective to improvement knowledge Mother pregnant at Ophir Health Center , West Pasaman It is recommended to midwife / health center For using video media in class Mother pregnant so that Mother pregnant can follow with happy and change Susana when giving education which mother is very enthusiastic about to video content and watch the video until finished , through educational videos prevention of stunting can exposed with clear because of there is picture and sound.